Brucine-Loaded Ethosomal Gel: Design, Optimization, and Anti-inflammatory Activity - Abdallah, Marwa H.; Lila, Amr S. Abu; Unissa, Rahamat; Elsewedy, Heba S.; Elghamry, Hanaa A.; Soliman, Mahmoud S. (AAPS PharmSciTech, 2021)
Brucine, one of the natural medications obtained from Nux vomica seeds, is used as an anti-inflammatory drug. Several investigations were performed to overcome its drawbacks, which will affect significantly its pharmaceutical formulation. The goal of the current investigation was to design, optimize, and evaluate the anti-inflammatory performance of BRU ethosomal gel. Brucineethosomal formulations were prepared using thin film hydration method and optimized by central composite design approach using three independent variables (lecithin concentration, cholesterol concentration, and ethanol percentage) and three response variables (vesicular size, encapsulation efficiency, and skin permeation). The optimized formulation was examined for its stability and then incorporated into HPMC gel to get BRU ethosomal gel. The obtained BRU-loaded ethosomal gel was evaluated for its physical properties, in vitro release, and ex vivo permeation and skin irritation. Finally, carrageenan-induced rat hind paw edema test was adopted for the anti-inflammatory activity. The developed BRU ethosomal gel exhibited good physical characteristics comparable with the conventional developed BRU gel. In vitro release of BRU from ethosomal gel was effectively extended for 6 h. Permeation of BRU from ethosomes was significantly higher than all formulations ( p < 0.05), since it recorded steady state transdermal flux value 0.548 ± 0.03 μg/cm 2 h with enhancement ratio 2.73 ± 0.23. Eventually, BRU ethosomal gel exhibited potent anti-inflammatory activity as manifested by a significant decrease in rat hind paw inflammation following 24 h. In conclusion, the study emphasized the prospective of ethosomal gel as a fortunate carrier for intensifying the anti-inflammatory effect of Brucine.